Effect of dietary astaxanthin on reproductive performance, egg quality and larvae of clowfish Amphiprion ocellaris (Cuvier, 1830) - Hue, Nguyen Thi Nguyet; Lam, Ho Son; Ngoc, Dao Thi Hong; Tram, Dang Tran Tu; Sang, Huynh Minh; An, Dinh Truong; Than, Doan Van; Tai, Nguyen Truong Tan; Dang, Do Hai; An, Hua Thai (Vietnam Journal of Marine Science and Technology, 2021)
This study was designed to evaluate the effects of astaxanthin in broodfish diets on reproductive performance, egg quality and larvae quality parameters of clownfish (Amphirion ocellaris). Five treatments were tested with 5 levels of astaxanthin (Carophyll Pink 10% CWS) of 0, 50, 100, 150 and 200 mg/kg added to the feed. Each treatment was repeated in triplicate and the supplemental feeding trials were arranged for 13 months. The results showed that there were significant differences in hatching rate of egg, malformed rate and survival rate of larvae in 3 days post-hatch (p<0.05) among the feeding trials of astaxanthin supplements. The highest hatching rate of egg and survival rate and the lowest malformed rate of larvae were observed in the treatment that was supplemented with astaxanthin 150 mg/kg feed, respectively 92.14 %; 93.57 % and 0.55 %. However, the astaxanthin supplementary diets did not affect the re-maturation and spawning period, spawning frequency, fecundity, egg diameter and larval size of nemo fish among the treatments. The results also suggested that astaxanthin requirement for clownfish broodstock to improve reproductive performance was 150 mg/kg feed.